In Vitro Antioxidant Activities of the Aqueous and Methanolic Stem Bark Extracts of (Schum.) - Gervason Moriasi MSc; Anthony Ireri PhD; Mathew Piero Ngugi PhD (SAGE Publishing, 2020)
Oxidative stress has been recognized as a key driver of many ailments affecting humankind. Free radicals attack biologically important biomolecules, impairing their functioning, thereby initiating and exacerbating diseases. As a comeback, antioxidant therapies have been proposed as novel approaches to ameliorating oxidative stress-associated diseases including chronic ones. Antioxidants are thought to employ multifaceted and multitargeted mechanisms that either restore oxidative homeostasis or prevent free radical buildup in the body, which overwhelm the endogenous defenses. Plants have been used for many ages across time to manage human diseases, and have a host of antioxidant phytocompounds. Piliostigma thonningii is traditionally used for the management of inflammation, malaria fever, rheumatism, and insanity, among other diseases caused by a disturbed redox state in the body. In this study, in vitro antioxidant activities of the methanolic and aqueous stem bark extracts of P. thonningii were evaluated using the in vitro antilipid peroxidation, the 1,1-diphenyl-2-picryhydrazyl (DPPH) free radical scavenging, and the ferric reducing antioxidant power assay methods. The obtained results revealed remarkable antioxidant activities of the studied plant extracts as evidenced by the low IC 50 and EC 50 values. These antioxidant activities could be due to the presence of antioxidant phytochemicals like flavonoids, carotenoids, tannins, and phenols, among others. Therefore, the therapeutic potency of this plant could be due to its antioxidant properties. This study recommends in vivo antioxidant efficacy testing of the studied plant extracts, as well as isolation and characterization of bioactive antioxidant compounds that are potent against oxidative stress.